Business power and the state in the Central Andes Bolivia, Ecuador, and Peru in comparison - Crabtree, John 1950-; Durand, Francisco 1950-; Wolff, Jonas 1975- (University of Pittsburgh Press, 2023)
"This coauthored monograph examines how business groups have interacted with state authorities in the three central Andean countries from the mid-twentieth century through the early twenty-first. This time span covers three distinct economic regimes: the period of state-led import substitutive industrialization from the 1950s through the 1970s, the neoliberalism of the 1980s and 1990s, and the post-neoliberal period since the earlier 2000s. These three countries share many similarities but also have important differences that reveal how power is manifested. Peru has had an almost unbroken hegemony of business elites who leverage their power over areas of state activity that affect them. Bolivia, by contrast, shows how strong social movements have challenged business dominance at crucial periods, reflecting a weaker elite class that is less able to exercise influence over decision-making. Ecuador falls in between these two, with business elites being more fragmented than in Peru and social movements being weaker than in Bolivia. The authors analyze the viability of these different regimes and economic models, why they change in specific circumstances, and how they affect the state and its citizens."
Literaturverzeichnis: Seite 225-252, Register
Keywords: Elite / (DE-627)091356881 / (DE-2867)16658-0; Entwicklung / (DE-627)091357322 / (DE-2867)10513-0; Öffentliches Unternehmen / (DE-627)091381169 / (DE-2867)11628-6; Volkswirtschaft / (DE-627)091398843 / (DE-2867)10025-6; Wirtschaftspolitik / (DE-627)091401143 / (DE-2867)10987-4; Peru / (DE-627)091382920 / (DE-2867)17928-6; Ecuador / (DE-627)091355753 / (DE-2867)17920-1; Bolivien / (DE-627)091352495 / (DE-2867)17914-3; Government business enterprises / Andes Region; BUSINESS & ECONOMICS / Business Ethics; Andes Region / Economic policy